Políticas Internas del Municipio Del Cantón Baba - Sandoya alvarado, Edith Margarita (2018)
The Autonomous Decentralized Government of the Baba Canton, which is the institution object of the case study, has an Organizational Structure that is constantly growing whose activity is to provide services to satisfy and improve the basic needs of citizens, always seeking the cantonal development improving the quality of life of its inhabitants.